Prospects for Gigabit Broadband: Examining whether Google's fiber strategy portends a new round of investment and competition in local access networks - David P. Reed (International Telecommunications Society (ITS), 2018)
This paper examines the question of whether the local access network environment stands on the cusp of significant change, one characterized by investment in new Gigabit broadband networks operated by a new breed of service providers. The highprofile Google Fiber project first deployed in the Kansas City metro area in 2012, soon followed by the more limited progress of the project in 2016, poses the strategic question of whether Google has "cracked the code" to identify and develop a viable business model for overbuilding local access networks. Based on a "top-down" estimate of the potential costs of deployment, this analysis finds that four business-model innovations pursued by Google, and now other players, can improve the economics of new network deployment to a significant degree under some realistic conditions, and, lacking any response from incumbents, therefore would improve the prospects for new entry of service providers in some areas. Incumbent broadband providers, however, are forming competitive responses that are substantially boosting the speed of their own broadband services in areas where Google Fiber is being deployed. The key takeaway from this analysis is that whether deployed by new entrants or incumbents, the "provein" point for Gigabit broadband networks is becoming lower, with the result that this technology will likely be deployed on an increasing basis in those areas where residential broadband consumers demonstrate a strong demand for the Gigabit service. One of the key policy issues raised by this outcome is the degree to which policy makers are comfortable with the resulting patchwork of fiber network deployment throughout a geographic region.
Keywords: 330